Age and gender differences in the level of motor docility, selected cognitive and motor-cognitive abilities of olderschool-age children - Beáta Ružbarská; Peter Kačúr; Monika Vašková; Erika Chovanová (Journal of Kinesiology and Exercise Sciences)
Background: The purpose of the study was to extend knowledge about the level of motor docility and selected cognitive and motor-cognitive abilities among secondary school students. Materials and Methods: A total of 43 children participated in the study. The Iowa Brace test was administered to assess the motor docility level. The motor-cognitive abilities were assessed by the Witty SEM system. The cognitive abilities were assessed by psychological tests that focused on attention, intellectual potential, and memory. The Mann-Whitney U test was used to determine the significance of gender differences in the level of motor docility and selected cognitive and motor-cognitive abilities of the students. The Kruskal-Wallis analysis of variance was used to determine the significance of differences between age groups. Results: The results indicate a low level of motor docility and cognitive abilities which may be caused by the quantity and quality of the acquired motor experience. Conclusion: Significant differences were observed in tests assessing the speed of thinking (BSQ) and in the mean reaction time in the speed of thinking test (BSRT), especially between the group with the lowest level of motor docility (0-4 points) and the group with a motor docility level at 10-12 points.